We have to solve the following system of equations by substitution.

- x^2 - y^2 = 9

- x - y = 1

x - y = 1

=> x = 1 + y

Substitute this for x in x^2 - y^2 = 9

=> (1 + y)^2 - y^2 = 9

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve the following system of equations by substitution.

- x^2 - y^2 = 9

- x - y = 1

x - y = 1

=> x = 1 + y

Substitute this for x in x^2 - y^2 = 9

=> (1 + y)^2 - y^2 = 9

=> 1 + y^2 + 2y - y^2 = 9

=> 1 + 2y = 9

=> 2y = 8

=> y = 4

x = 1 + y

=> 1 + 4

=> 5

**We get x = 5 and y = 4**